PRODUKTIVITAS TENAGA KERJA PADA PROYEK PEMBANGUNAN REVITALISASI DAN PENGEMBANGAN ASRAMA HAJI WAIHERU AMBON - Tomabuji Talaohu; Tonny Sahusilawane; Maslan Abdin (Journal Agregate, 2023)
The revitalization and construction of the Waiheru Ambon hajj dormitory building, the method used in this research is the validation test, reliability test, f test and t test using the SPSS V16 tool where in this method the questionnaire data will be obtained which will then be analyzed with the SPSS V16 tool. The research results were obtained based on the results of data analysis that has been carried out to solve the problem in this research where when conducting research on project implementation such as column casting work, it is often found that the workforce is not effective and efficient when pressing the vibrator so that when dismantling the formwork you can see many columns. which is corroded, then obtained: 1) The positive influence between competence on labor productivity can be seen from the t-count of  5.149 > t-table 1.724 and sig value = 0.000 < 0.05 which means that competence is very influential in influencing labor productivity. 2) The positive effect between skills on labor productivity can be seen from the t-count of 3.732 > t table 1.724 and sig value = 0.001 < 0.05 which means that skills is very influential in influencing labor productivity. 3) The positive effect of work discipline on labor productivity can be seen from the t-count of 11.992 > t-table 1.724 and sig value = 0.000 < 0.05 which means that work discipline is very influential in influencing labor productivity. 4) The positive influence between the level of income on labor productivity can be seen from the t-count 3.968 > t-table 1.724 and sig value = 0.001 < 0.05 which means that the level of income is very influential in influencing labor productivity.